An improvised two in one syringe suction drain for surgeries of extremities - Kamath, J B; Kamath, R K; Bansal, H (Indian Journal of Plastic Surgery, 2005)
Use of an improvised two in one syringe suction drain is being presented for a case with two adjacent non-communicating surgical wounds following release of Duputryn′s contracture primarily involving the longitudinal band of the palmar fascia of the hand, in line with the middle and ring finger. Instead of using two separate closed suction drainage system we modified our method by using a 3 way cannula which could accept 2 draining tubes to be connected to one 50cc syringe with negative suction pressure.
Keywords: Improvised Syringe Suction Drain; Threeway cannula